Multiphase and Multistakeholder English Translation Processes Behind Subtitling Chinese Auteur Films: An Actor-Network Theory Perspective - Sun, Xichen (Journal of Audiovisual Translation, 2023)
The professional translation processes involved in subtitling Chinese auteur films are under-reported in audiovisual translation literature. The present study investigates the translation processes employed for Chinese films destined for an international audience with a focus on fifth- and sixth-generation directors’ films. These film auteurs depict China’s diverse cultural elements and contemporary social reality, for which English subtitles provide an essential bridge to connect to an international audience. Interview data collected from ten established Chinese-to-English translators/subtitlers, whose names are credited in the selected films, identify two remarkable features of subtitling these contemporary Chinese auteur films: Multiple phases of the translation processes employed across the filmmaking lifespan and multiple stakeholders involved in the wider translation processes beyond translators/subtitlers. Actor-Network Theory is used to elicit interwoven relationships among the various human and non-human actors connected to translating/subtitling activities across different stages of filmmaking. These findings confirm that translating/subtitling is not an isolated post-production task but rather permeates all filmmaking phases. This can be a key factor in contributing to overall quality, which is critical in disseminating subtitled films by some of China’s most celebrated auteurs. Lay summary The international film market has increasingly featured Chinese films, especially the works by established Chinese directors, such as Zhang Yimou, Chen Kaige, Jia Zhangke and Jia Zhangke. Their films reflect China’s cultural conventions and contemporary social reality. English subtitling is the most popular mode of translation to distribute Chinese films among the English-speaking audience. However, little is known about the agents involved in translating the Chinese high-profile films and the translation processes. To fill this knowledge gap, we interviewed ten translators or subtitlers contributing to the translation of the four aforementioned directors. The collected interview data inform us that many other stakeholders (e.g. directors, producers, screenwriters, distributors and subtitle editors) play a role in the shaping of the final English subtitles shown on the screen, and translation of Chinese films takes place throughout the whole filmmaking process (i.e. film development, pre-production, post-production, distribution and exhibition). A sociological framework is adopted to demonstrate the interwoven relationships among the various human (i.e. translators/subtitlers and other stakeholders) and non-human actors (i.e. accompanying materials and translation products) connected to translating/subtitling activities across different stages of filmmaking. It is argued that such a multiphase and multistakeholder process helps to improve the overall quality of Chinese film subtitling.